1991
DOI: 10.1038/bjc.1991.316
|View full text |Cite
|
Sign up to set email alerts
|

Palliation and life quality in lung cancer; how good are clinicians at judging treatment outcome?

Abstract: Summary A recent trial by the MRC Lung Cancer Working Party used physician assessments to compare two palliative schedules of radiotherapy in lung cancer. A prospective study has been undertaken on a subset of these trial patients to see how physician assessments of symptomatic relief and general condition correlate with patient perception of therapeutic response. In 40 patients followed up monthly from presentation until close to death, good agreement was found between doctors and patients on change in specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…it would be unethical to rechallenge a patient with morphine after a satisfactory outcome on an alternative opioid.) Other studies have shown some reliability in how good clinicians are at judging treatment outcomes [17]. Our study shows that 87% (41/47) morphine non-responders did improve when switched to an alternative opioid suggesting that side effects were morphine related although we accept that we could not control for all other variables.…”
Section: Discussioncontrasting
confidence: 50%
“…it would be unethical to rechallenge a patient with morphine after a satisfactory outcome on an alternative opioid.) Other studies have shown some reliability in how good clinicians are at judging treatment outcomes [17]. Our study shows that 87% (41/47) morphine non-responders did improve when switched to an alternative opioid suggesting that side effects were morphine related although we accept that we could not control for all other variables.…”
Section: Discussioncontrasting
confidence: 50%
“…It seems plausible that patients' ratings of their general health and QoL should contribute more to prediction alongside clinical variables than self-rated symptoms or functional status, as the latter to some extent can be assessed by others, although not perfectly. Although clinicians are reasonably able to assess observable symptoms, they are poor at assessing patients' QoL (Fowlie et al, 1989; Regan et al, 1991). However, if HRQoL measures make their greatest contributions to prediction of survival by measuring global health/QoL, a more comprehensive generic measure may add more predictive value than cancer-specific measures that include symptoms, particularly in situations where clinical information is already fairly comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there may be a rather low concordance between raters (20) although the interobserver variability was very low in another study (21). This variability is probably also not as large when relative changes are evaluated, rather than when a single recording is done (22). Taken together, it is our belief that differences in the recording of data did not influence the results to any relevant degree, and, in particular, that they did not modify the interpretations of the potential merits of the CBR evaluation.…”
Section: Discussionmentioning
confidence: 86%